(untitled) (PJDOL, 2023)
The rapid developments and growing population in the world are of serious concern for environmental damages in the recent years. The environmental challenges faced by almost all countries due to pollution of water, air and soil are inestimable. In order to combat the menace of environmental pollution and human hygiene, there is huge need of mass awareness on the environment and use of natural resources among the society. The formal systems of environmental education cater only a part of the need and augment the research and developments. T